The third bullet [large type] : a Bob Lee Swagger novel - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel., 2013)
Former Marine sniper Bob Lee Swagger investigates the events of November 22, 1963, and the third bullet that so decisively ended the life of John F. Kennedy. Swagger is asking questions that few have asked before: Why did the third bullet explode? Why did Lee Harvey Oswald, about to become the most hunted man on earth, risk it all by returning to his rooming house to secure a pistol he easily could have brought with him? How could a conspiracy that went unpenetrated for fifty years have been thrown together in the two and a half days between the announcement of the presidential route and the assassination itself? As Bob investigates, another voice enters the narrative: that of a gifted veteran of the CIA Plans Division. Hugh Meachum has secrets and the means and the will to keep them buried.